Developing an Evidence-Based Policy Model for Iranian Public Health System (qualitative research) (پژوهش‌های مدیریت عمومی, 2014)
All governments to solve the problems facing their communities improve conditions and taking advantage of opportunities, the mechanisms are invoked in the name of public policy. To improve the quality of such policies, several models have been proposed, one of the newest fashion, is evidence-based policy-making. Evidence-based policy-making in the health sector has been welcomed by many countries. The purpose of this research is to design a model for the institutionalization of evidence-based policy-making in the health sector of the country. By means of qualitative research (interviews with senior policy makers and health care system and policy analysis foundation interviews) and extract key themes, to the institutional model of evidence-based policy design. Relationships between variables were examined. At the end of the study findings were analyzed and proposed solutions to overcome barriers that limit the use of evidence-based policy-making in the health care system were presented.